Integration of AI Tools in Islamic Education Curriculum Development Management: Challenges and Opportunities - Karim, Ahmad Atho'ul (Journal of Loomingulisus ja Innovatsioon, 2024)
The objective of this research is to introduce a model for development management curriculum imagein the application of AI on Islamic education. The method used in this research is by literature review, in discussing about the use of Artificial Intelligence (AI) on Islamic Education Curriculum. These sources include journals, books and research reports that have been subjected to thematic and cross-analysis for a determination of emerging trends and points of view. Literature Review : The relevance of AI model are important to the Islamic education which require for technologies such as Natural Language Processing (NLP), Machine Learning and Chatbot. The fourth area is NLP which is useful in text analysis and translation and it can be used in understanding of religious texts such as the Qur’an and hadith having a problem with the issue of translation. Machine learning provides the prediction and thus the learning personalization which helps to adapt the material to the student, yet it raises the issue of algorithm bias. One way that chatbots increase interactivity is in providing learning support in real time but these are the drawbacks because the information supplied must be correct. As a result, integrating concepts in Artificial intelligence in the Islamic education curriculum shall enhance personalization and learning of Islamic concepts as well as the acquisition of the 21st-century skills. But here, the concerns are mobility infrastructure readiness, how to get trainers, and moral problems, such as problem of set algorithms, and the problems with the use of the technology referring to the principles of Islam. However, the post induces expectations of improving the process of learning and the analysis of religious knowledge, meaning that the implementation of this method cannot disregard moral and religious principles.